Republic of Armenia : 2019 Article IV Consultation and Request for a Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Armenia. (IMF Staff Country Reports; Country Report ;, 2019)
This paper presents Armenia's 2019 Article IV Consultation report and request for a Stand-By Arrangement (SBA). The arrangement is intended to be precautionary. It will provide insurance against external shocks and support the authorities' efforts to strengthen economic fundamentals and policy frameworks. It will also help effective implementation of structural reforms, particularly relating to governance and improving business climate. Discussions focused on macroeconomic and structural policies to ensure macro and fiscal sustainability, foster higher and more broad-based growth, and strengthen resilience to shocks. Supported by the upgraded fiscal rule, fiscal consolidation remains on track, and public debt has started to decline. Inflation is under control, the financial system remains stable, and pressures on the exchange rate have been limited. The authorities' efforts are centered on advancing structural reforms to generate higher, more inclusive, and resilient growth; and strong policies to maintain macroeconomic stability.